"Fearful Dreams" in Thomas Kyd's Restored Canon. Issue 1 (7th February 2019) - Freebury-Jones, Darren
Abstract : This article utilizes a combination of digital and traditional literary-critical analysis in order to explore ominous dreams in the Elizabethan dramatist Thomas Kyd's undoubted plays The Spanish Tragedy (1587), Soliman and Perseda (1588), and Cornelia (1594). The article proceeds to explore the use of dreams in the anonymously printed early modern plays King Leir (1589) and Arden of Faversham (1590) in order to demonstrate that these works are in good accordance with Kyd's highly individual thought processes and overall dramaturgy. Close reading of these texts is accompanied by an examination of the characteristics of Kyd's verse style, as well as collocation matching, which provides quantitative and qualitative evidence for Kyd's idiosyncratic lexicon of words and phrases. This study extends and corrects the work of generations of attribution scholars and suggests that King Leir and Arden of Faversham can be ascribed to Kyd with a high degree of probability.